Primary subacute hematogenous osteomyelitis in children: A clearer bacteriological etiology. (June 2016) - Spyropoulou, Vasiliki; Dhouib Chargui, Amira; Merlini, Laura; Samara, Eleftheria; Valaikaite, Raimonda; Kampouroglou, Georgios; Ceroni, Dimitri
Background: This study aimed to describe the spectrum of pediatric primary subacute hematogenous osteomyelitis (PSAHO) and to investigate its bacterial etiology. Methods: Sixty-five consecutive cases of PSAHO admitted to our institution over a 16-year period (2000–2015) were retrospectively reviewed to assess their laboratory and radiographic imaging features, as well as their bacteriological etiology. Results: On evaluation, white blood cell count and C-reactive protein were normal in 53 (81.5 %) and 34 cases (52.3 %), respectively, whereas the erythrocyte sedimentation rate was superior to 20 mm/h in 44 cases (72.1 %). Blood cultures failed to identify the pathogen in all but one patient, and classic bone sample cultures only managed to isolate the pathogen in five cases (11.6 %). Use of polymerase chain reaction (PCR) assays on bone aspirates or blood allowed the causative microorganism to be isolated in a further 22 cases. Using classic cultures and PCR assays together resulted in pathogen detection in 27 cases (62.8 % of the children bacteriologically investigated), with Kingella kingae being the most frequently reported microorganism. Conclusions: Two distinct forms of PSAHO should be distinguished on the basis of age of patients and bacteriological etiology. The infantile form affects children aged between 6 months and 4 years and is predominantly due to K. kingae . The juvenile form involves children aged >4 years and Staphylococcus aureus appears to be the main bacteriological etiology. Appropriate nucleic amplification assays drastically improve the detection rate of the microorganisms responsible for PSAHO. Level of evidence: Case series, level IV.